Walking training augments the effects of expiratory muscle training in Parkinson's disease. (30th August 2021) - Oguz, Semra; Gurses, Hulya Nilgun; Kuran Aslan, Goksen; Demir, Rengin; Ozyilmaz, Semiramis; Karantay Mutluay, Fatma; Apaydin, Hulya
Abstract : Objectives: To investigate the effects of walking training combined with respiratory muscle training (RMT) on pulmonary function, respiratory muscle strength, and functional exercise capacity in patients with Parkinson's disease. Materials & Methods: Thirty patients with Parkinson's disease were included in the study. Patients were randomly divided into two groups: the walking and RMT group (W + RMT, n  = 15) and the RMT ( n  = 15) group. Spirometry, respiratory muscle strength, and a 6‐min walking test were measured before and after the eighth week of the study. RMT was performed using inspiratory and expiratory threshold loading methods. Walking training intensity was adjusted according to the 6‐min walking test. Patients performed 15 min of inspiratory muscle training and 15 min of expiratory muscle training in both groups, and 15 min of walking training in the W + RMT group in addition to RMT, twice per day, 5 days/week, for a total of 8 weeks at home. Training intensity was adjusted once per week for the groups at the hospital. Results: Respiratory muscle strength and 6‐min walking distance were significantly increased ( p  = .001), and UPDRS‐III scores were significantly improved (W + RMT: p  = .008 and RMT: p  = .01) in the two groups. The increase in maximal expiratory pressure was significantly higher in the W + RMT group than in the RMT group ( p  = .007). Conclusion: Walking training increases the effect of expiratory muscle training in patients with Parkinson's disease.